Harry Potter and the sorcerer's stone - Rowling, J. K. (A.A. Levine Books, 1998)
Rescued from the outrageous neglect of his aunt and uncle, a young boy with a great destiny proves his worth while attending Hogwarts School for Wizards and Witches.